Is the Beck Depression Inventory (BDI) a Useful Tool for Predicting IVF Success? - Dragiša Šljivancanin; Snežana Vidaković; Darija Kisić Tepavčević; Bojana Petrović; Una Šljivančanin; Milan Dokić (Medicina)
Background and Objectives: Infertility is a global problem. The interaction between depression and infertility seems bidirectional, and depression may negatively influence IVF outcomes. The Beck Depression Inventory (BDI) is one of the most extensively used instruments for diagnosing depression. The aim of this study was to assess the dynamics of depression in patients undergoing IVF utilizing the BDI. Materials and Methods: This prospective cohort study was conducted at the Clinic for Gynecology and Obstetrics of the University Clinical Center of Serbia in Belgrade, Serbia during the year 2019. Both partners in the IVF program were required to complete the paper-based BDI 5 to 10 days before starting ovarian stimulation, within the 48 h preceding oocyte aspiration and four weeks after embryo transfer. We sought to identify potential predictors of a favorable IVF outcome by using logistic regression modeling. Results: Our study enrolled 86 couples. The overall IVF efficacy in our cohort was 18.6%. A statistically significant logistic regression model (p = 0.001) managed to explain 47.6% of the variability. Increasing patient age, the presence of depression (BDI > 16) and the number of failed IVF cycles were found to be significant negative predictors of ongoing IVF success. Conclusions: Depression is more common in patients undergoing IVF than in the general population. Depression might increase the odds of IVF failure, lending credence to the idea that depression screening using BDI should be a routine part of the IVF process.